Nanoscale Topotactic Phase Transformation in SrFeOx Epitaxial Thin Films for High-Density Resistive Switching Memory - Tian, Junjiang (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.